Beep Beats of Banking and other Money Music: On the appearances of music in a selection of Danish TV commercials for fi nancial products - Jørgensgaard Graakjær, Nicolai (Danish Yearbook of Musicology, 2010)
Previous research on music in TV commercials has routinely highlighted financial products – notably banking – for the absence of music. It has been argued that music compromises integrity and respectability. Hence it is somewhat surprising that recent Danish TV commercials for financial products are filled with music. It seems as if these TV commercials represent an aesthetic avant-garde when it comes to the appearance of music. But why are these TV commercials for financial products so filled with music? And how does music contribute to the overall commercial messages? In answering these questions the article analyses the appearance of music in a selection of TV commercials for Danske Bank and Nordea. The article involves both synchronic and diachronic analysis: Firstly by analysing illustrative Danske Bank commercials from April 2004 to June 2008, secondly by analysing illustrative Nordea commercials from the same period of time for comparison. On a market including numerous products with functionally equivalent attributes – presenting so-called parity products – user-positioning is imperative. Denoting specific lifestyle characteristics becomes the main objective of advertising to the detriment of providing specific product information, for example. In this context, music is a highly significant commercial ingredient: All TV commercials analysed have music throughout, and the music is highly significant. Music plays a decisive role in convincing us that Danske Bank is for the rational, result-oriented, relatively young, high-tech elite, whereas Nordea is for the emotional, communion-oriented and caring idealist of all ages: Customers of Danske Bank apparently do what they individually do best and customers of Nordea apparently do what they in communion feel best about doing.